TINJAUAN TERHADAP PENGGUNAAN ASAS FIRST-TO-FILE DAN PRINSIP RELATIVE GROUND FOR REFUSAL OF REGISTRATION BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Fadillah, Moch Iqbal; Artati, Sri Untari Indah (Fakultas Hukum Universitas Trisakti, 2024)
In the practice of trademark registration in Indonesia, disputes frequently arise between trademark owners and the Trademark Appeal Board. These disputes typically occur when a trademark application is rejected due to its similarity to an already registered trademark. This study focuses on the application of the First-to-File principle the Relative Grounds for Refusal of Registration within the Indonesian trademark registration system. It aims to evaluate whether the considerations made by the Substantive Examiner in deciding trademark registration cases are in line with the principle of relative grounds for refusal of registration, as stipulated in Law No. 20 of 2016 on Trademarks and Geographical Indications.The research methodology employed is a normative juridical approach with a descriptive nature. The study relies on secondary data obtained through a literature review, which is then analyzed qualitatively. The conclusions are drawn deductively based on an analysis of the applicable laws and regulations. The findings of this research indicate that the application of the First-to-File principle and relative grounds for refusal of registration in the decisions made by the Substantive Examiner is consistent with the provisions set forth in Articles 3 and 21 of Law Number 20 of 2016. However, the study also highlights challenges in the application of these principles, which may affect the transparency and objectivity of the decisions made by the Trademark Examiner.